Assessing Assumptions: Surveying Diversity within Nonprofit Radio Stations in Canada - King, Gretchen (2023)
The nonprofit radio sector in Canada includes over 180 community and Indigenous stations. Studies of nonprofit radio programming note the diversity of on-air content from news to music, which is in line with the sector’s mandate. However, does the assortment of content translate into a diversity of individuals behind the microphone? And who is taking decisions in station management and governance. To better understand the equity practices found within nonprofit radio, this article highlights the results of an online survey to quantify the diversity found among the board members, volunteers, and employees who operate these stations.